KAJIAN PEMBERIAN ASAM ASKORBAT (VITAMIN C) DENGAN KONSENTRASI YANG BERBEDA TERHADAP KETENGIKAN ABON IKAN LELE (Clarias batrachus) - Aryani Aryani; Evnaweri Evnaweri (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2014)
This research study about of the added ascorbic acid with different concentrate on fish abon rancidity which storage on day-1 and day-15, the parameters is chemist and organoleptic. Contribute from this researchs are to know the optimally ascorbic acid concentrate on make fish abon. This research use 4 (four) treatments are: no added ascorbic acid, added ascorbic acid 1%, 2% and 3%. Result from this research are added ascorbic acid with the different concentrate no significant to water basis but to lipid, rancidity and organoleptic significant and very significant inter treatment, which treatment A is the best during day-1 storage, and treatment D is the best during day-15storage.